Research on the impact of the development of green finance in the China region on residents’ health - Fan, Shuhao; Kong, Fanchao; Li, Cheng (Frontiers in Public Health, 2023)
In the context of implementing the strategy of "Double Carbon" and "Healthy China", this paper firstly measures the level of green finance development and the comprehensive index of health care accessibility in each province by using the entropy weight method based on 30 provincial panel data from 2007 to 2021. A panel fixed effects model was also used to empirically analyze the effect of regional green finance development on the improvement of residents' health. In addition, a panel threshold model was constructed to empirically test the threshold effect of green finance on residents' health under the influence of four external environments: carbon intensity level, healthcare accessibility, residents' living standard and human capital level.The empirical results show that the regional green financial development in China significantly improves the health level of residents. And the impact has significant regional heterogeneity, as shown in the improvement effect is more significant for the provinces in the central and western regions. In addition, the impact of green financial development on the health level of residents in China is non-linearly influenced by external environmental factors. The improvement effect of green finance on residents' health level is more significant in the provinces with higher carbon intensity level, residents' living standard, human capital level and lower accessibility to medical services.In this regard, regional governments should continue to build and optimize a synergistic development ecosystem of green finance and public health, give full play to the advantages of financial leverage, promote green, low-carbon and high-quality economic and social development, and realize the beautiful vision of harmonious coexistence between human beings and nature.